Association between depressive symptoms and pulse wave velocity is mediated by increased adiposity in older adults with type 2 diabetes - Moh, Mei Chung (J Psychiatry Neurosci, 2021)
BACKGROUND: Studies investigating the association between depression and aortic stiffness in older patients with type 2 diabetes are lacking. We postulated an association between depressive symptoms and aortic stiffness, and this relationship may be mediated by increased adiposity. METHODS: We analyzed participants with type 2 diabetes aged 55 years or older (n = 958). We measured aortic stiffness using carotid–femoral pulse wave velocity (cut-off ≥ 12 m/s) using the tonometry method. We defined depressive symptoms as a score of greater than 5 on the Geriatric Depression Scale–15 (GDS-15). Adiposity indices we assessed were body mass index, waist circumference, waist-to-height ratio, visceral fat area and fat mass. RESULTS: Among the participants, 27.2% had aortic stiffness, of whom 6.5% had depressive symptoms. Score on the GDS-15 was correlated with pulse wave velocity, and both variables were correlated with the adiposity markers we analyzed (all p < 0.05). Depressive symptoms were associated with pulse wave velocity (B = 1.79, 95% confidence interval [CI] 0.83–2.75) or aortic stiffness (risk ratio 1.60, 95% CI 1.10–2.33) in the unadjusted model. The association persisted after controlling for demographics, duration of diabetes, glycated hemoglobin, comorbidities and medications. Further adjustment for visceral fat area and fat mass in separate models reduced the association between depressive symptoms and pulse wave velocity or aortic stiffness. Mediation models revealed that the mediation proportions of fat mass and visceral fat area on the association between depressive symptoms and pulse wave velocity were 11.8% and 9.7%, respectively. A preliminary analysis of longitudinal data (n = 184) showed similar findings. LIMITATIONS: Causality cannot be inferred from the associations we observed. CONCLUSION: Depressive symptoms are associated with elevated pulse wave velocity in older people with type 2 diabetes, and this relationship may be partially mediated by increased adiposity.